Influence of cross-linker polarity on selectivity towards lysine side chains - Fiala, Jan; Kukačka, Zdeněk; Novák, Petr (Journal of proteomics, 2020)
The combination of chemical cross-linking and mass spectrometry is currently a progressive technology for deriving structural information of proteins and protein complexes. In addition, chemical cross-linking is a powerful tool for stabilizing macromolecular complexes for single particle cryo-electron microscopy. Broad pallets of cross-linking chemistry, currently available for the majority of cross-linking experiments, still rely on the amine-reactive N-hydroxysuccinimide esters targeting mainly N-termini and lysine side chains. These cross-linkers are divided into two groups: water soluble and water insoluble; and research teams prefer one or another speculating on the benefits of their choice. However, the effect of cross-linker polarity on the outcome of cross-linking reaction has never been studied. Herein, we use both polar (bis(sulfosuccinimidyl) glutarate) and non-polar (disuccinimidyl glutarate) cross-linkers and systematically investigated the impact of cross-linker hydrophobicity on resulting distance constraints, using bovine serum albumin as a model protein. SIGNIFICANCE: Even though the amine reactive BS2G and DSG cross-linkers have the same length of spacer and are based on N-hydroxysuccinimidic group, our data showed that each of them formed preferentially different cross-links. We demonstrated that the choice of cross-linker can have a significant impact on the output data for structural characterization of biomolecules. Using equimolar mixtures of DSG with d6-BS2G, and BS2G with d6-DSG, we established that the polar BS2G preferentially bound to polar regions of modified molecule, whereas non-polar DSG bound to hydrophobic regions. This phenomenon established that the mixture of polar and non-polar cross-linkers acted as an efficient tool for the determination of distance constraints in proteins.
Keywords: Lysine; lysin; Disuccinimidyl glutarate; reagencia zkříženě vázaná; Cross-Linking Reagents; Bis(sulfosuccinimidyl) glutarate; hmotnostní spektrometrie; Bovine serum albumin; Chemical cross-linking; Protein structure; Serum Albumin, Bovine; sérový albumin hovězí; elektronová kryomikroskopie; Mass Spectrometry; Structural mass spectrometry; Cryoelectron Microscopy